Development an honesty and discipline assessment instrument in the integrated thematic learning at elementary school - Ari Setiawan; Syarief Fajaruddin; Dinar Westri Andini (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
Honest and discipline as learning outcomes need to be assessed. Many teachers have difficulty developing honesty and discipline assessments. The lack of honest and discipline assessment instruments require special attention in development. The purposes of this developmental research were to find out: (1) honest and discipline instrument indicators; (2) content validity of the instrument; (3) construct validity of the instrument; (4) instrument reliability and (5) instrument application for assessment. The research method used the development of affective instruments. The research subjects were 140 students of grade IV and V on the elementary school. The instrument used a peer-assessment model with a summative rating scale. Data analysis technique used content validity with Aiken index; construct validity with Exploratory Factor Analysis (EFA); reliability with Cronbach; and application of instrument with descriptive quantitative. The results of the study were indicators of honest assessment instruments and discipline of the peer-assessment model, consisted of 4, honest: convey the true information and do the examination independently. Discipline: come to school on time and obey the rules of the school. The content validity of the developed assessment instruments based on the theory had fulfilled and included in the high category. The construct validity for the developed instrument had fulfilled; means, all items were valid. Reliability of the developed instrument had met the requirements; means, the instruments were reliable. The developed instruments can be used for assessment and proved by the use of instruments for honest and disciplined assessment of elementary school students.